2021
DOI: 10.1108/jd-02-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

“I found what I needed, which was a supportive community”: an ethnographic study of shared information practices in an online cosplay community

Abstract: PurposeThis study explored the information practices of cosplayers, as well as the social norms, social types and information infrastructure of an online cosplay Facebook group, the Rey Cosplay Community (RCC).Design/methodology/approachTo better understand individual behavior, the authors made use of ethnographic methods and semi-structured interviews. Observation of the RCC was combined with information gleaned from select participant interviews.FindingsThe results suggest that the RCC can be conceived of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Our current study adds to the body of serious leisure research by exploring the information practices of cosplayers, thereby building on the small number of publications (e.g., Hill and Pecoskie, 2017;Hirsch, 2021;Vardell et al, 2020;Vardell et al, 2022) that have explored fan studies through the lens of information behaviour. Price (2017) investigated the information behaviour of fan groups on the Internet in her doctoral dissertation, where she found that the organization of fans' works was usually based on the community-generated ontology.…”
Section: Information Practices and Personal Information Management Fo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our current study adds to the body of serious leisure research by exploring the information practices of cosplayers, thereby building on the small number of publications (e.g., Hill and Pecoskie, 2017;Hirsch, 2021;Vardell et al, 2020;Vardell et al, 2022) that have explored fan studies through the lens of information behaviour. Price (2017) investigated the information behaviour of fan groups on the Internet in her doctoral dissertation, where she found that the organization of fans' works was usually based on the community-generated ontology.…”
Section: Information Practices and Personal Information Management Fo...mentioning
confidence: 99%
“…This, too, was noted by Hirsch (2021), who documented a variety of creative information literacy practices employed by cosplayers. In a study on fans' use of an online community to obtain information about making costumes, Vardell et al (2020) and Vardell et al (2022) found that wellorganized online communities could provide significant assistance for making costumes. However, there has been little research on the information practices of cosplayers and how fans manage and organize information obtained from online communities.…”
Section: Information Practices and Personal Information Management Fo...mentioning
confidence: 99%
“…Some people argue that cosplay promotes unrealistic beauty standards and encourages fans to obsess over fictional characters. Others argue that cosplay is a harmless hobby that allows fans to express their creativity and connect with like-minded individuals (Vardell et al, 2022).…”
Section: The History Of Cosplayingmentioning
confidence: 99%